Poi Sanglong/Poi Khamsang : The Study of Rite of Passage in Tai man’s life in Tai Yai Community of Ban Pangmoo Village, Maehongson, Thailand and Tai Aiton Community of Banlung Mantai , Karbi Anglong District, Assam, India. - et. al., Wanlaya Namtham, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Poi is the word in Tai which means festival, celebration and religious ceremony. This paper studies on Poi Sanglong of Tai Yai of Ban Pangmoo, Maehongson, Thailand and Poi Khamsang of Tai Aiton of Banlung, Poi Sanglong and Poi Khamsangis the Buddhist ceremony and life cycle ceremony among the Tai boys (the age from 7 to 21 years old) who are ordained and become as novice monks. Participant observation and in-depth interview are the method of this study. Both of Tai groups reside in different country and settle down far from each other but Poi Sanglong and Poi Khamsang have been practicing in both communities. These two Pois share same meaning and function; firstly Sanglong and Khamsang are used to call novice monk and have same cultural root, secondly Poi Sanglong and Poi Khamsangshare the same pattern of socialization, and lastly these Pois reflect Tai ethnic identity through the process of the ritual. Tai Yai at BanPangmoo, Maehongson, Thailand migrated from Mawkmai, Mong Nai and Lankher Shan state to Thailand in the nineteenth century as well as Tai Aiton at Banlung Mantai, Karbi Anglong district, Assam, India migrated from Chindwin Valley, Kachin state to India because of the war. Thus, both of the Tai groups maintain their own ethnic identity through culture and practices. Poi Sanglong and Poi Khamsang are one of the important rituals in one Tai man’s life as rite of the passage. Moreover, Poi Sanglong or Poi Khamsang is the celebration of the ethnic identity among the Tais.